Secure Data Transmission in ECU Data Acquisition Systems based on MQTT and TLS - Bedretchuk, João Paulo; Dopke, Tiago Porsch; Martins, Thiago; Gracioli, Giovani; Spengler, Anderson Wedderhoff (Anais do Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares (SSV); 2025: Anais do II Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas VeicularesDO - 10.5753/ssv.2025.39498, 2025)
Electronic Control Units (ECUs) play a critical role in modern automotive systems, providing data for performance analysis, calibration, and validation. Traditional commercial acquisition tools are widely used but often limited by high costs, dependency on high-performance computers, and restricted integration with modern cloud and edge-processing infrastructures. To overcome these limitations, we developed the Intelligent Acquisition and Analysis System for ECUs (IASE), an embedded platform designed for real-time data acquisition and calibration. This paper presents a secure communication architecture for the second generation of the system (IASE v2), enabling remote connectivity through 4G networks while ensuring confidentiality, integrity, and authenticity of transmitted data. The architecture integrates MQTT over TLS with per-device certificates and mutual authentication (mTLS). We validate the solution through experiments under real-world 4G conditions, demonstrating reliable performance, secure Over-The-Air (OTA) updates, and message delivery consistency. Results show that the proposed approach ensures robust data security without compromising scalability, making it suitable for modern automotive testing environments.